2007
DOI: 10.1190/1.2435171
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between near-surface electromagnetic soil parameters and early-time GPR signals: An experimental study

Abstract: We explore a new approach to evaluate the effect of soil electromagnetic parameters on early-time ground-penetrating radar (GPR) signals. The analysis is performed in a time interval which contains the direct airwaves and ground waves, propagating between transmitting and receiving antennas. To perform the measurements we have selected a natural test site characterized by very strong lateral gradient of the soil electrical properties. To evaluate the effect of the subsoil permittivity and conductivity on the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 11 publications
3
52
0
1
Order By: Relevance
“…It is the obvious consequence of the increasing of the dielectric permittivity of soil when the moisture content increases. Some authors showed that the amplitude of the reflected GPR signal decreases as the soil humidity increases (Pettinelli et al, 2007).…”
Section: Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the obvious consequence of the increasing of the dielectric permittivity of soil when the moisture content increases. Some authors showed that the amplitude of the reflected GPR signal decreases as the soil humidity increases (Pettinelli et al, 2007).…”
Section: Simulationsmentioning
confidence: 99%
“…The algorithm estimates the shallow soil properties using the early-time arrivals, i.e. the arrivals recorded before subsurface reflections arrive (Pettinelli et al, 2007). The amplitude and shape of the early-time arrivals change with soil permittivity, conductivity, and antenna standoff.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the use of electromagnetic induction (EMI) and electrical resistivity for measurements of soil electrical conductivity (Sudduth et al, 2001), magnetic susceptibility for measuring soil contamination by heavy metals (Jordanovaa et al, 2008), ground penetrating radar (GPR) for measurements of soil water content (Pettinelli et al, 2007), proximal passive γ-ray spectrometry for measuring K, U, Th, sand, clay and iron contents , cameras to measure soil colour and estimate soil organic carbon and iron contents (Sudduth and Hummel, 1988;Viscarra Rossel et al, 2008), diffuse reflectance spectroscopy using visible-near infrared (vis-NIR) and mid infrared (mid-IR) energies to estimate soil organic carbon (OC), clay content, mineral composition and other soil properties (e.g. BenDor and Banin, 1995;Stenberg et al, 1995;Reeves and McCarty, 2001;Shepherd and Walsh, 2002;Demattê et al, 2004;Brown et al, 2006;Viscarra Rossel et al, 2006a), ion-sensitive field effect transistors (ISFET) and ion-selective electrodes to measure soil pH, lime requirement and soil nutrients (Adamchuk et al, 1999;Viscarra Rossel and Walter, 2004;Adamchuk et al, 2005;Viscarra Rossel et al, 2005;Sethuramasamyraja et al, 2008), and mechanical draft systems for measuring soil strength (Hemmat and Adamchuk, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Alterações nas propriedades petrofísicas do meio relacionadasàs variações dos teores de umidade nos poros se traduzem em diferenças nas propriedades elétricas do meio (permissividade dielétrica e condutividade elétrica), e consequentemente em mudanças nos atributos da onda no seu percurso. Pettinelli et al (2007), restringindo a análise do atributo amplitudè a janela temporal que contém apenas o registro da onda direta, sugeriram seu emprego para a estimativa da variação espacial do teor de umidade da subsuperfície rasa.…”
Section: Introductionunclassified